Understanding experiences and perceptions of perinatal mental health screening tools among under-served groups: A qualitative study of women from ethnic minority communities in the United Kingdom - Ngozika Jane Hemuka; Laura Kudrna; Lina Martino; Jason Copp; Samina Saudagar; Kimberley Maynard (PLoS ONE, 2026)
Background Perinatal mental health problems, such as depression and anxiety, are major global public health concerns. Screening for mental health problems in pregnancy supports early detection and treatment, improving outcomes for women and their families. However, mental ill health is not consistently identified in routine maternal practice, particularly among women from ethnic minority communities in high income countries like the United Kingdom. Although research has explored mental health screening tools among majority ethnic populations, there remains a notable lack of evidence regarding the experiences of women from ethnic minority communities. To address this, this study investigated these women’s perceptions of perinatal mental health screening tools used by United Kingdom maternity services. Methods A qualitative study of women’s experiences and perceptions of perinatal mental health screening tools. Purposive sampling strategy was employed to recruit women from ethnic minority communities from a local charity to participate in online and face-to-face semi-structured interviews and a focus group discussion. Participants were asked about their understanding of and experience with the Generalized Anxiety Disorder scale (GAD), Edinburgh Postnatal Depression Scale (EPDS) and Whooley questions . Data were collected on perceptions of what made it easy or hard to be screened using these tools. Analyses were conducted using a framework analysis approach. Results Fifteen women took part in the study (12 in interviews; 3 in a focus group), representing Asian, Black African, Bangladeshi, Black Caribbean, Pakistani, and Afghan ethnic backgrounds. Four organising themes were identified after coding. These were: Mixed experiences and perceptions of perinatal mental health screening tools; Factors shaping women’s perceptions and engagement with perinatal mental health screening tools: barriers and facilitators; Lack of continuity, early support, and clear pathways hinders women’s engagement with mental health screening tools; and Recommendations for improvement. Conclusions The detection of mental health problems among women from under-represented communities can be improved by considering the identified themes. Key opportunities include being more explicit and culturally sensitive about mental health, explaining the purpose and benefits of screening tools, its process, and potential outcomes and consequences. It is important to allocate sufficient time, ensure privacy during mental health screening appointments, incorporate open-ended questions and avoid ambiguous words in screening tools. The use of mental health screening tools in the perinatal period needs to be delivered in a supportive context in order to address health and health inequalities.